STRATEGI PENGENTASAN KEMISKINAN TERHADAP PENURUNAN RUMAH TANGGA MISKIN DI KOTA DENPASAR - Kartika, I Nengah (Buletin Studi Ekonomi; Vol 18, No. 1,Februari 2013. (PP 1-84), 2013)
According to a report published by Denpasar Government , the number of poor households (RTM) in Denpasar experienced a decline in 2010 compared with 2006. The problem is whether and how far the program / poverty reduction strategies defined and followed up by the Government of Denpasar. In this study, data were collected by interview and observation. The results showed that the number of RTM declined during 2007-2011, but still left some RTM of the total population of Denpasar. Most of the existing RTM welfare states because of government assistance in the form of goods, home improvement, scholarships, JKBM, or other assistance. Some aid programs can not be developed further by the recipient because of resource constraints.
Keywords: poverty reduction and poor households